Focusdata: Foreign Policy through Language and Sentiment. Issue 2 (2nd February 2022) - Fisher, Scott; Klein, Graig R; Codjo, Juste
Abstract: Countries routinely translate official statements and state media articles from native languages to English. Over time, these articles provide a window into what each government is trying to portray to the world. The FOCUSdata Project provides years' worth of text and language sentiment ratings for hundreds of thousands of articles from state media and ministry of foreign affairs' websites from North Korea, China, Russia, and Iran. Information is an important foreign policy tool and national security strategists analyze how it influences the attitudes and behaviors of foreign audiences. This article introduces the FOCUSdata Project and shows how the sentiment data provide unique abilities to analyze Russia's and Iran's reactions to US policies and events and NGO human rights campaigns. Evaluating countries' official narratives improves understanding of government signals to outside actors, reactions to crises and foreign policy tools, and interests regarding (un)favorable developments. Governments' sentiment provides unique explanatory power.